(untitled) (JURNAL ADMINISTRASI PUBLIK, 2018)
One of the government entity is to give direct and indirect service to the society in the district or Kecamatan. As the government sub-system in Indonesia, Kecamatan has the strategic position to play the functional role in governance, service, administration, development also for the society itself. Camat has important role in implementing the society’s empowerment. The empowerment model by the government is to give positive impact in business development and economic empowerment for the society. Through certain program, so many benefit can be obtained by the society in order to create society’s improvement in culture, social and economic in Likupang Timur. Keywords; The role of Sub-district Head, Community Empowerment